METODE PELAKSANAAN PEKERJAAN BOREPILE, PILECAP DAN PIER KOLOM PADA PEKERJAAN JEMBATAN KEDONDONG TOL CISUMDAWU SEKSI 5B - Wardani; Heryadiana, Asep Dian (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Transportation is an inseparable part of human survival. Related to human activities,transportation plays a very significant role in social, economic, environmental and other aspects.Tol Road is a public and closed road where its construction is charged to cross according to theapplicable tariffs. This road is a form of tariff grant on the road that is generally applied to coverthe cost of construction and maintenance of the road. Tol Road Cisumdawu is one of the road freeof barriers that crosses from the area of Cileunyi, Sumedang, Dawuan. This Tol road is no morethan an effort to streamline traffic to improve the distribution of goods and services that grow theeconomy around, as well as become one of the fast access between the districts of the city. A bridgeis a building that allows a road to cross a river, valley or other road of different elevations. In theplanning of the bridge must take into account the functional needs of transportation. This journalfocuses on methods of implementation of pile bore, pilecap, as well as pier work located on theconstruction project of Road Tol cisumdawu section 5 b located in the village of cipelangkecamatan ujungjaya sumedang.